1998
DOI: 10.1002/j.1550-8528.1998.tb00377.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Age on Protein Conservation during Very‐Low‐Energy Diet in Obese Sprague‐Dawley Rats

Abstract: JOHNSON, JULIA A, CHOON-HIE YU, MEI-UlH YANG, F. XAVIER PI-SUNYER. Effect of age on protein conservation during very-low-energy diet in obese SpragueDawley rats. Obes. Res. 1998;6:448--457. Objective: To examine the effect of age on body protein losses occurring during severe energy restriction in obesity. Research Methods and Procedures: Weanling (young) Sprague-Dawley rats (YR) were fed a high fat (35% energy) diet (HFD) until mean body weight approached that of a group of chow-fed retired breeder (aged) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…We also observed that the most marked decrease in tissue protein masses concerned the splanchnic organs (small intestine, liver) and cardiac muscle, while only little or no difference was observed in the skeletal muscles. A previous study in rodents has already shown that during CR, the liver and heart are more prone to protein loss than skeletal muscles [32]. As the use of AA for protein synthesis in muscles is preserved during CR on a high-protein diet [33,34,35], the moderate decrease in protein mass likely resulted from an increase in proteolysis and AA allocation to oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed that the most marked decrease in tissue protein masses concerned the splanchnic organs (small intestine, liver) and cardiac muscle, while only little or no difference was observed in the skeletal muscles. A previous study in rodents has already shown that during CR, the liver and heart are more prone to protein loss than skeletal muscles [32]. As the use of AA for protein synthesis in muscles is preserved during CR on a high-protein diet [33,34,35], the moderate decrease in protein mass likely resulted from an increase in proteolysis and AA allocation to oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…However, one of the most important goals of restricted diets for obese individuals is the maintenance of their body protein mass [12], because skeletal muscle is a key contributor to the adjustments in energy and amino acid metabolism during long periods of reduced dietary energy consumption [13].…”
Section: Introductionmentioning
confidence: 99%